Avaliação da suplementação intranasal de oxigênio em burros (Equus caballus x Equus asinus) anestesiados com a associação cetamina, butorfanol e éter gliceril guaiacólico - Módolo, Tiago José Caparica [UNESP] (2014)
The main complications of the field anesthesia in the mules are incident of hypoxemia and paucity of studies on anesthetic protocols in the species. The aim of this study was to evaluate the effect of intranasal oxygen supplementation (SIO) in mules (Equus caballus X Equus asinus) anesthetized under field conditions with combination of ketamine, butorphanol and guaifenesin. Six adult mules (278 to 365 kg) were used and underwent to premedication with 0.2 mg/kg of midazolam (i.m.), after 15 min, 0.02 mg/kg of detomidine (i.v.), after 5 min, anesthesia was induced with administration (free flow) a mixture of 5% guaifenesin with ketamine (2.0 mg/ml) and butorphanol (22.5 μg/ml) (C/B/G). When lateral recumbency occurred, the same mixture was used to maintenance (2.1 ml/kg/h). The animals were submitted twice to the MPA, induction and maintenance of anesthesia described above, with a minimum interval of 20 days, thus forming two experimental groups. WITHOUT SIO – MPA, induction (0.92 ± 0.24 ml/kg (mean ± SD)) and maintenance (2.2 ± 0.2 ml/kg/h) with C/B/G mixture without SIO; WITH SIO - MPA, induction (0.98 ± 0.17 ml/kg) and maintenance (2.3 ± 0.4 ml/kg/h) with C/B/G mixture with SIO in rate of 40 ml/kg/min. Arterial blood was collected each 20 minutes (T0, T20, T40 and T60) during anesthesia, for blood gas analysis, and the cardiovascular parameters measured each 5 minutes. The data were analyzed by repeated measures ANOVA followed by Bonferroni test and P values < 0.05 were considered significant. Hypoxemia (PaO2 < 60 mmHg) was observed in mules of the group without SIO at all times evaluated (T0 = 59 ± 5; T20 = 55 ± 5; 53 ± 7 = T40; T60 = 49 ± 8) and the means were considered significantly lower than the mean the supplemented group (T0 = 160 ± 34; T20 = 115 ± 34; T40 = 92 ± 25; T60 = 81 ± 19). Furthermore, the animals showed cardiovascular stability, demonstrating that the ...